The Utilization of E-Commerce to Improve The Competitiveness of Msmes inPajagalan Village, Sumenep District - Risqi, Sandi Hafifi; Zamzami, Muftil Umam Ilham; Homaidi, Homaidi; Ramadani, Ramadani (Universitas Mercu Buana, 2024)
With the increasingly rapid development of technology and information, people are familiar with the internet and need constant access to it. A new lifestyle is emerging, namely shopping on the internet or e-commerce. E commerce is not only used by large corporations but also by micro, small and medium businesses. The research was conducted to determine the benefits of e-commerce to increase the competitiveness of MSMEs in Pajagalan village, Sumenep sub-district, Sumenep district. Using descriptive research methods with qualitative analysis. The findings show that MSME revenues increase through e-commerce, making the products sold more widely known and attracting customers more easily. Therefore, e-commerce makes it possible to save advertising costs and increase transaction speed. Therefore, it will increase the competitiveness of MSMEs in Pajagalan Village, Sumenep District, Sumenep Regency.